Threat of Exit by Non‐Blockholders and Income Smoothing: Evidence from Foreign Institutional Investors in Japan* - David, Parthiban; Duru, Augustine; Lobo, Gerald J.; Maharjan, Johan; Zhao, Yijiang (Contemporary Accounting Research, 2022)
ABSTRACT We examine how the threat of exit by non‐blockholders (investors with ownership <5%) relates to firms' income smoothing. Unlike informed blockholders, non‐blockholders lack private information and therefore rely more on reported accounting numbers to evaluate firm performance. To isolate the exit threat, we use the unique setting in Japan where strong firm‐centric social norms and lack of insider access lead non‐blockholding foreign institutions to influence management primarily through the threat of exit. We predict and find that foreign non‐blockholders' exit threat is positively associated with the extent of income smoothing. This effect is more pronounced for firms less embedded in Japan's stakeholder‐based system, firms with greater stock liquidity, and firms with higher US institutional ownership. In addition, smoothing associated with such an exit threat, on average, is informative. Our findings suggest that Japanese firms under non‐blockholders' exit threat increase income smoothing to reduce perceived uncertainty and that such smoothing generally meets non‐blockholders' information needs.